A systematic review of UK‐based long‐term nonsurgical interventions for people with severe obesity (BMI ≥35 kg m−2). Issue 3 (6th February 2020) - Aceves‐Martins, M.; Robertson, C.; Cooper, D.; Avenell, A.; Stewart, F.; Aveyard, P.; de Bruin, M.
Abstract: Introduction: The aim of this project was to systematically review UK evidence on the effectiveness of long‐term (≥12 months) weight management services (WMSs) for weight loss and weight maintenance for adults (≥16 years) with severe obesity (body mass index ≥35 kg m −2 ), who would generally be eligible for Tier 3 services. Methods: Four data sources were searched from 1999 to October 2018. Results: Our searches identified 20 studies, mostly noncomparative studies: 10 primary care interventions, nine in secondary care specialist weight management clinics and one commercial setting intervention. A programme including a phase of low energy formula diet (810–833 kcal day −1 ) showed the largest mean (SD) weight change at 12 months of –12.4 (11.4) kg for complete cases, with 25.3% dropout. Limitations or differences in evaluation and reporting (particularly for denominators), unclear dropout rates, and differences between participant groups in terms of comorbidities and psychological characteristics, made comparisons between WMSs and inferences challenging. Conclusions: There is a persistent and clear need for guidance on long‐term weight data collection and reporting methods to allow comparisons across studies and services for participants with severe obesity. Data could also include quality of life, clinical outcomes, adverse events, costs and economic outcomes. A randomised trial comparison of National Health Service Tier 3 services with commercial WMSs would be of value. Abstract : This work systematically review UK evidence on the effectiveness of long‐term (≥12 months) weight management services for weight loss and weight maintenance for adults (≥16 years) with severe obesity (body mass index ≥35 kg m −2 ), who would generally be eligible for Tier 3 services in the National Health Service.